1990
DOI: 10.1111/j.1524-4725.1990.tb00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Keratoacanthoma of the Eyelid: “Malignant” Keratoacanthoma or Squamous Cell Carcinoma?

Abstract: We report an aggressive keratoacanthoma of the upper eyelid that recurred at the site of a previously excised keratoacanthoma. The diagnosis was confirmed by biopsy. Because the surgery required would be extensive, medical therapy was tried first. The tumor was treated with intralesional injections of 5-fluorouracil and radiotherapy. Despite this therapy, the orbital computed tomogram showed tumor extension into the orbit, and an orbital exenteration was performed. Histopathology of the excised tumor was consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…KA progressing to SCC with metastatic spread is rare; however, KA-like SCCs are not uncommon. 1,42,44,50,[66][67][68][69] In addition, KA may have increased aggressive potential in immunosuppressed patients. The progression of a KA into SCC in a patient with Hodgkin's disease receiving polychemotherapy has been observed; this raises the question of whether the transformation into SCC may have resulted from a mutagenic effect of the chemotherapy.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…KA progressing to SCC with metastatic spread is rare; however, KA-like SCCs are not uncommon. 1,42,44,50,[66][67][68][69] In addition, KA may have increased aggressive potential in immunosuppressed patients. The progression of a KA into SCC in a patient with Hodgkin's disease receiving polychemotherapy has been observed; this raises the question of whether the transformation into SCC may have resulted from a mutagenic effect of the chemotherapy.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…Furthermore, as there have been rare reports of metastasis with KAs, many dermatologists now simply manage them as any other nonmelanoma skin cancer. 29,30 As the details of this controversy exceed this review, in this section, the management of KA will be discussed alongside invasive SCC.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…In its otiginal description, KA was considered a clinically and histologiciilly distinct lesion (1). However, as data has accumulated, incltiding the findings of aggressive ancl metastatic KAs, many investigators have concluded that KA is a type of squamous cell carcinoma with potential for involution as well as aggressive behavior and metastasis (2)(3)(4)(5)(6)(7)(8). Studies regarding oncogenesis have demonstrated similar mutant p53 protein expression in KAs and WD-SCCs, supporting the concept that KA is a type of WDSCC (9).…”
mentioning
confidence: 97%